Psittacosaurus houi, a longer snouted psittacosaurid from the Lower Cretaceous Lujiatun Unit of Yixian Formation, China, with the synonymy of the unresolved genus Hongshanosaurus revisited - Ishikawa,Asato; Zheng,Wenjie; Imai,Takuya; Hattori,Soki; Shibata,Masateru; Kawabe,Soichiro; Jin,Xingsheng (PeerJ, 2025)
The taxonomic validity of some genera and species within Psittacosauridae has been disputed, including that of Hongshanosaurus houi, which has been synonymized with Psittacosaurus lujiatunensis previously. To assess the validity of the former genus and species and elucidate the taxonomy and diversity in Psittacosauridae, we describe a nearly complete psittacosaurid skull (ZMNH M12414) with the aid of computed-tomography techniques. The specimen comes from the Lujiatun Unit of the Lower Cretaceous Yixian Formation, Liaoning, northeastern China, which has also produced Psittacosaurus major, P. lujiatunensis, and H. houi. ZMNH M12414 exhibits a series of unique features that are also present in the adult referred skull of H. houi (IVPP V12617), indicating that both specimens are attributable to the same species within Psittacosauridae. The proportionally large length of the snout used to diagnose H. houi cannot be used for taxonomic distinction of Psittacosaurus because this character is also found in P. amitabha, supporting that the genus Hongshanosaurus is a junior synonym of Psittacosaurus. On the other hand, ZMNH M12414 and IVPP V12617 exhibit a set of features that are not observed in any other species of Psittacosaurus, including P. lujiatunensis. Because of these features, the specimen in question better fits as its own species within Psittacosaurus: P. houi. A phylogenetic analysis supports the validity of P. houi, where the specimens form an independent species within Psittacosaurus. The computed-tomography techniques employed in the present study facilitated re-assessment of the taxonomy and morphological diversity of Psittacosaurus, and its application is encouraged for previously described dinosaur taxa whose validities are in question. By utilizing such techniques, the detailed evaluation of ontogenetic, intraspecific, and interspecific variations will be crucial to understand the true taxonomy and diversity of Psittacosaurus in future studies.
Keywords: Morphology; Phylogeny; Psittacosaurus; Hongshanosaurus; Taxonomy; Cretaceous; Ceratopsia; Dinosaur